Supervision of Graduate Students - Holdaway, Edward; Deblois, Claude; Winchester, Ian (Canadian Journal of Higher Education, 1995)
Graduate education is an essential component of universities; it also contributes substantially to national economies. However, problems in graduate education, especially with respect to completion and quality, have emerged in many countries, including Canada. To address these problems and related issues and practices, a comprehensive three-year research project has been conducted involving questionnaires and interviews in Canada, Australia, Great Britain, and other countries. This paper presents information from questionnaires completed in 1993 by 736 supervisors of graduate students in 37 universities across Canada. Many substantial differences were obtained between the means for items when respondents were classified into eight discipline areas. The responses related to master's and doctoral programs were generally similar.